2013
DOI: 10.4021/gr575w
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors and Clostridium Difficile Infection: Are We Propagating an Already Rapidly Growing Healthcare Problem?

Abstract: Proton pump inhibitors (PPIs) have been associated with Clostridium difficile infection (CDI) in several recent studies. The exact mechanism through which PPIs may cause Clostridium difficile infection is not well understood. One potential mechanism to explain this association may be that elevated gastric pH levels facilitate the growth of potentially pathogenic upper and lower gastrointestinal tract flora. Although Clostridium difficile spores are acid resistant, vegetative forms are susceptible to acidity. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…This makes being on immunosuppressants an independent risk factor for recurrent CDI as shown in a previous study [15]. In the past few years, multiple studies and meta-analysis have shown a significant relationship between PPI use and the risk of CDI while some studies have rejected this hypothesis [16][17][18]. Our study did not show a causal relationship between PPI use and recurrence of CDI.…”
Section: Discussionsupporting
confidence: 52%
“…This makes being on immunosuppressants an independent risk factor for recurrent CDI as shown in a previous study [15]. In the past few years, multiple studies and meta-analysis have shown a significant relationship between PPI use and the risk of CDI while some studies have rejected this hypothesis [16][17][18]. Our study did not show a causal relationship between PPI use and recurrence of CDI.…”
Section: Discussionsupporting
confidence: 52%
“…The use of proton pump inhibitors has also been linked to the development of microscopic colitis. 16,17 8. Cardiovascular PPI use and cardiovascular events have also been researched extensively, but no firm conclusions have been reached because these relative risks are masked by other factors.…”
Section: Gastrointestinalmentioning
confidence: 99%
“…51 Proposed mechanisms include the promotion of intestinal pathogen growth related to elevated gastric pH, impairment of leukocytes, inhibition of the protective effect of gastric acid on proliferation of C. difficile spores, or specific antimicrobial properties of proton pump inhibitors (PPIs). 52 Data related to specific gastric acid-suppressing agents and CDI risk are conflicting. In 2014, a large retrospective study of ICU patients found that PPI therapy was independently associated with CDI and that the risk of CDI was higher with PPIs versus histamine 2 receptor antagonists (3.8% vs 2.2%, respectively, p<0.01).…”
Section: Acid Suppressionmentioning
confidence: 99%
“…Although meta‐analyses have suggested an association between gastric acid suppression and both primary and recurrent CDI risk, the exact mechanism to explain this increased risk remains unclear . Proposed mechanisms include the promotion of intestinal pathogen growth related to elevated gastric pH, impairment of leukocytes, inhibition of the protective effect of gastric acid on proliferation of C. difficile spores, or specific antimicrobial properties of proton pump inhibitors (PPIs) . Data related to specific gastric acid–suppressing agents and CDI risk are conflicting.…”
Section: Acid Suppressionmentioning
confidence: 99%